Membranes for Cation Transport Based on Dendronized Poly(Epichlorohydrin-Co-Ethylene Oxide). Part 2: Membrane Characterization and Transport Properties - Alireza Zare (MDPI AG, 2021)
In this paper, we report on the preparation and characterization of membranes out of two side-chain liquid crystalline copolymers, dendronized at two different extents (20 and 40%, CP20 and CP40, respectively). The membranes were characterized by atomic force microscopy (AFM), field-emission scanning electron microscopy (FESEM), contact angle (CA) analysis, and water uptake. Moreover, transport properties were studied by methanol and proton conductivity experiment and by linear sweep voltammetry (LSV). For the sake of comparison, the behavior of the grafted copolymers was compared with the unmodified copolyether CP0 and with Nafion 117. Results demonstrated that in CP20 and CP40, cation transport depends on the presence of defined cationic channels, not affected by water presence; the comparison between LSV experiments performed with different alkaline cations suggests that CP40 possesses channels with larger diameters and better-defined inner structures.